2014
DOI: 10.1371/journal.pone.0087433
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Flow Dynamics in the Obstructed and Stented Ureter by Means of a Biomimetic Artificial Model

Abstract: Double-J stenting is the most common clinical method employed to restore the upper urinary tract drainage, in the presence of a ureteric obstruction. After implant, stents provide an immediate pain relief by decreasing the pressure in the renal pelvis (P). However, their long-term usage can cause infections and encrustations, due to bacterial colonization and crystal deposition on the stent surface, respectively. The performance of double-J stents - and in general of all ureteric stents - is thought to depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 38 publications
8
54
0
Order By: Relevance
“…This higher friction might create a pressure loss, which reduces the flow outside the stent. Therefore, we account that urine flow dynamics is a more complex mechanism than only a difference in stent and ureter diameters, as observed in the work of Clavica et al We observed indeed that the used procedures here lead to results (i.e., encrustation compositions and morphologies of the crystals found on the stent surfaces) similar to what reported in other in vitro case studies . In addition, the obtained data seem to well simulate the behavior of what reported in real‐case in vivo studies and in particular for even longer indwelling times of the stents .…”
Section: Discussionsupporting
confidence: 87%
“…This higher friction might create a pressure loss, which reduces the flow outside the stent. Therefore, we account that urine flow dynamics is a more complex mechanism than only a difference in stent and ureter diameters, as observed in the work of Clavica et al We observed indeed that the used procedures here lead to results (i.e., encrustation compositions and morphologies of the crystals found on the stent surfaces) similar to what reported in other in vitro case studies . In addition, the obtained data seem to well simulate the behavior of what reported in real‐case in vivo studies and in particular for even longer indwelling times of the stents .…”
Section: Discussionsupporting
confidence: 87%
“…The volumetric inlet flow rate was set to 1 mL•min −1 , while a 0 gauge pressure boundary condition was imposed at the device outlet. The imposed value of volumetric flow rate was chosen to replicate a physiologically relevant condition, in accordance with previous studies [20][21][22][23]. A no-slip boundary condition was set at the channel walls.…”
Section: Cfd Simulations Of the Flow Field Within Soc Modelsmentioning
confidence: 99%
“…A few studies have reported a numerical simulation of urine flow in a straight, stented ureter model [4][5][6][7][8], while other studies have analyzed urine flow in a curved, stented ureter model [9,10] were performed for mild or no ureteral stenosis, and they demonstrated that the flow through the side holes either could not be visualized or was very small. However, the studies did not evaluate the flow through the side holes in a stented ureter model for various severities of ureteral stenosis.…”
Section: Introductionmentioning
confidence: 99%